Crystal structure of ricin toxin A chain complexed with a highly potent pterin-based small-molecular inhibitor - Masaru Goto; Natsumi Sakamoto; Shoko Higashi; Rena Kawata; Kazuki Nagatsu; Ryota Saito (Taylor & Francis Group, 2023)
Ricin toxin A chain (RTA), from Ricinus communis, is a deadly protein that inactivates ribosomes by degrading an adenine residue at position 4324 in 28S rRNA. Recently, we have demonstrated that pterin-7-carboxamides with peptide pendants were potent RTA inhibitors. Among these, N-(pterin-7-carbonyl)glycyl-L-tyrosine (7PCGY) is the most potent RTA inhibitor as a small organic molecule. However, despite this fascinating inhibitory activity, the mode of interaction of 7PCGY with RTA remains elusive. This study aimed to elucidate the factors responsible for the high RTA inhibitory activity of 7PCGY based on X-ray crystallographic analysis. Herein, we report the successfully resolved X-ray crystal structure of 7PCGY/RTA complexes, revealing that the interaction between the phenolic hydroxy group in 7PCGY and Asn78 of RTA through a hydrogen bonding and the conformational change of Tyr80 and Asn122 are responsible for the high RTA inhibitory activity of 7PCGY.